(3GdCQHYjf aj CUhd GdOjfs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3Gddge EfaYfG eeG YdeJfG hYdefG eG jfaYfG SHMGf GdeJaQO ai bjheJI dhLhH GdCRdjI hGdHbGA s
(3BNQgG (B:s
(3jG Cgd GdJbhi hCgd GdeZaQg Bejf jG QH GdYGdejf Ke GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI ai HjQhJ s
Keywords: (3GdJhMjO hGdedd hGdfMds